Slaves to fashion : poverty and abuse in the new sweatshops - Ross, Robert J. S., 1943- (University of Michigan Press, 2004)
Supported by carefully researched evidence, the author traces the 20th century fall and tragic rebirth of sweatshop conditions in the American apparel industry.